Stimulating and Nurturing Professionalisms, Creativity and Innovation in Organization - Menara Simanjuntak; Haryadi Sarjono (Bina Nusantara University, 2011)
Knowledge management is an emerging discipline and professionalism, creativity, innovation, organization and teams need to be thought about in this new context. This paper creates a framework in which to discuss these concepts with literature research. It goes on to explore how our professionalisms, creativity and innovations is blocked in variety ways, including deep-seated beliefs about the world. The need for professional skills today in workplace faces a number of challenges, especially in unfamiliar and unpredictable situations. Finally this paper takes a brief look at two tools to support knowledge management, professionalisms, creativity and innovations - one in the human domain and the other in the technology domain. We are also needs to boost its capacity for continuous professionalism, creativity and innovation for both technology, social, economic, and organization reasons.